PENGARUH MANAJEMEN NYERI TERHADAP PENURUNAN TINGKAT NYERI KEPALA PADA PASIEN HIPERTENSI DI RUANG IGD RS LABUANG BAJI MAKASSAR - Satriana Satriana; Tutik Agustini; Suci Hardiyanti; Sudarman (CV. Adiba Aisha Amira, 2026)
Hypertension is a chronic condition often causing headaches due to increased blood pressure that affects cerebral circulation and induces muscle tension. This symptom impacts patient comfort and quality of life. Pain management can be delivered pharmacologically or non-pharmacologically. One effective non-pharmacological method is a warm compress, which works through vasodilation, improved circulation, and muscle relaxation. This scientific work applied a case report on a 63-year-old male patient with hypertension who presented to the Emergency Department of RSUD Labuang Baji Makassar with a headache rated 6 on the pain scale. After a warm compress intervention, pain decreased to a score of 3. The results show that warm compresses effectively reduce pain intensity and improve patient comfort. This method can be considered a simple, practical, and applicable nursing intervention.